1996
DOI: 10.1021/om960716w
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Route to Organoplatinum or Platinum−Palladium Dendrimers

Abstract: A new divergent route to organotransition-metal dendrimers is described, in which a key step involves oxidative addition. The product dendrimers contain organoplatinum(IV) centers in each inner generational layer and either platinum(II) or palladium(II) centers in the outermost layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…The reactor was flushed with 10 reactor volumes and the amounts of palladium and phosphorus on both sides of the membrane were determined by ICP-AES. The retention of 13-[Pd(allyl)Cl] 12 was 99.7%, indicating that the catalyst, which was in the Pd II state, was stable under these conditions. During the catalytic cycle the catalyst also becomes Pd 0 , and so we attempted a retention measurement of the catalyst in the Pd 0 state.…”
Section: Continuous Processmentioning
confidence: 98%
See 4 more Smart Citations
“…The reactor was flushed with 10 reactor volumes and the amounts of palladium and phosphorus on both sides of the membrane were determined by ICP-AES. The retention of 13-[Pd(allyl)Cl] 12 was 99.7%, indicating that the catalyst, which was in the Pd II state, was stable under these conditions. During the catalytic cycle the catalyst also becomes Pd 0 , and so we attempted a retention measurement of the catalyst in the Pd 0 state.…”
Section: Continuous Processmentioning
confidence: 98%
“…[63] The two doublets in the 31 P{ 1 H} NMR spectrum of 12-(PdMeCl) 4 (at δ ϭ 31.3 and 2.75; J ϭ 39.0 Hz) clearly showed the coupling of the inequivalent phosphorus atoms. For 13-(PdMeCl) 12 the coupling between these atoms could not be observed, because the signals had broadened significantly. However, the two signals found in the 31 P{ 1 H} NMR spectrum at δ ϭ 30.8 and 2.38 suggested that cis complexes were formed.…”
Section: Formation Of the Palladium Complexesmentioning
confidence: 99%
See 3 more Smart Citations